2013
DOI: 10.7314/apjcp.2013.14.2.723
|View full text |Cite
|
Sign up to set email alerts
|

Low Level of Consanguinity in Moroccan Families at High Risk of Breast Cancer

Abstract: Background: Breast cancer is worldwide the most common cancer in women and is a major public health problem. Genes with high or low penetrance are now clearly implicated in the onset of breast cancer, mostly the BRCA genes. All women in families at high risk of breast cancer do not develop tumours, even when they carry the familial mutation, suggesting the existence of genetic and environmental protective factors. Several studies have shown that consanguinity is linked to a decreased or an increased risk of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The results showed that age at the diagnosis of disease, hepatospleenomegaly and subtype of ALL was comparable among consanguineous and non-consanguineous patients however consanguineous showed signi cantly protective impact age at diagnosis of disease (Table 2). This is in concordance with the previous studies performed in highly consanguineous populations of Middle East that suggests that consanguinity confers protective effect to the development of the adult cancers at an early age (26)(27)(28). In the previous studies, different germ line genetic variations have been associated with the chemotherapy related cardiotoxicity (29,30).…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that age at the diagnosis of disease, hepatospleenomegaly and subtype of ALL was comparable among consanguineous and non-consanguineous patients however consanguineous showed signi cantly protective impact age at diagnosis of disease (Table 2). This is in concordance with the previous studies performed in highly consanguineous populations of Middle East that suggests that consanguinity confers protective effect to the development of the adult cancers at an early age (26)(27)(28). In the previous studies, different germ line genetic variations have been associated with the chemotherapy related cardiotoxicity (29,30).…”
Section: Discussionsupporting
confidence: 92%
“…29 – 32 However, several studies had shown that countries with high consanguinity demonstrate lower age-standardized mortality rates and incidence in breast cancer,. 15 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…The mutational spectrum of BRCA1/2 in the Moroccan population is becoming partially characterised thanks to local genetic centers, who have developed oncogenetic consultations for familial forms of breast and ovarian cancers and performed molecular analyses of BRCA genes using the conventional individual exon-by-exon Sanger sequencing (10,13,14,16,17). Thus, several mutations in two particular genes have been reported in the Moroccan National Genetic Database (http:// ethnos.findbase.org/home-ma).…”
Section: Discussionmentioning
confidence: 99%